Seq and You Will Find - Schonrock, Nicole; Jonkhout, Nicky; Mattick, John S. (Current Gene Therapy, 2016)
The human genome sequence is freely available, nearly complete and is providing a foundation of research opportunities that are overturning our current understanding of human biology. The advent of next generation sequencing has revolutionized the way we can interrogate the genome and its transcriptional products and how we analyze, diagnose, monitor and even treat human disease. Personal genetic profiles are increasing dramatically in medical value as researchers accumulate more and more knowledge about the interaction between genetic and environmental factors that contribute to the onset of common disorders. As the cost of sequencing plummets, whole genome sequencing of individuals is becoming a reality and the field of personalized genomic medicine is rapidly developing. Now there is great need for accurate annotation of all functionally important sequences in the human genome and the variations within them that contribute to health and disease. The vast majority of our genome gives rise to RNA transcripts. This extraordinarily versatile molecule not only encodes protein information but also has great structural dynamics and plasticity, capacity for DNA/RNA/protein interactions and catalytic activity. It is a key regulator of biological networks with clear links to human disease and a more comprehensive understanding of its function is needed to maximise its use in medical practice. This review focuses on the complexity of our genome and the impact of sequencing technologies in understanding its many products and functions in health and disease.
Keywords: Capture-sequencing